2020
DOI: 10.1002/jmv.26709
|View full text |Cite
|
Sign up to set email alerts
|

Interpretative immune targets and contemporary position for vaccine development against SARS‐CoV‐2: A systematic review

Abstract: The year 2020 started with the emergence of novel coronavirus, severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), which causes COVID‐19 infection. Soon after the first evidence was reported in Wuhan, China, the World Health Organization declared global public health emergency and imminent need to understand the pathogenicity of the virus was required in limited time. Once the genome sequence of the virus was delineated, scientists across the world started working on the development of vaccines. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 92 publications
0
17
0
2
Order By: Relevance
“…For millions of people who have received the new vaccines, few side effects, if any, and vaccine development continue at an increasing pace [ 7 ]. Real-world safety monitoring and reporting is established in most countries.…”
mentioning
confidence: 99%
“…For millions of people who have received the new vaccines, few side effects, if any, and vaccine development continue at an increasing pace [ 7 ]. Real-world safety monitoring and reporting is established in most countries.…”
mentioning
confidence: 99%
“…It is not the only such approach in the context of the development of a vaccine preparation against SARS-CoV-2. The list of preclinical and clinical trials also includes an attenuated influenza vector vaccine (BiOCAD Global), a recombinant influenza A vaccine (Rospotrebnadzor) and an attenuated influenza virus vector expressing the S protein from SARS-CoV-2 (Fundação Oswaldo Cruz and Instituto Buntantan) [107].…”
Section: Covid-19 Mucosal Vaccines Currently Under Developmentmentioning
confidence: 99%
“…A number of COVID-19 vaccines have been approved and are in human clinical trials in the United States as of October 27, 2020. 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 Covid-19 vaccine side effects and warnings are described as short-term side effects that were observed in leading vaccine trials 52 , 53 and post marketed vaccine administration and include: Injection site pain and redness 84%, Fatigue 63%, Myalgia, or muscle pain 14.8%, Arthralgia or joint pain 24%, Headache 55%, and Fever 14%. On December 8, 2020, the United Kingdom reported that two patients who were injected with Pfizer's recently approved coronavirus vaccine had to be treated for serious adverse reactions, which has led to warnings that those with “significant” allergies may not be able to get the vaccine.…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%